Viral density and virus-to-bacterium ratio in deep-sea sediments of the Eastern Mediterranean - Danovaro, R; Serresi, M (Applied and environmental microbiology, 2000)
Viruses are now recognized as a key component in pelagic systems, but their role in marine sediment has yet to be assessed. In this study bacterial and viral densities were determined at nine deep-sea stations selected from three main sites (i.e., the Sporades Basin, the Cretan Sea, and the Ierapetra Trench at depths of 1,232, 1,840, and 4,235 m, respectively) of the Eastern Mediterranean. The three areas were characterized by different phytopigment and biopolymeric carbon concentrations and by changes in the protein and carbohydrate pools. A gradient of increasing trophic conditions was observed from the Sporades Basin (North Aegean) to the Ierapetra Trench (South Aegean). Viral densities (ranging from 1 x 10(9) to 2 x 10(9) viruses ml of sediment(-1)) were significantly correlated to bacterial densities (n = 9, r(2) = 0.647) and reached values up to 3 orders of magnitude higher than those generally reported for the water column. However, the virus-to-bacterium density ratio in deep-sea sediments was about 1 order of magnitude lower (range of 2 to 5, with a modal value of 2.6) than in pelagic environments. Virus density decreased vertically with depth in sediment cores at all stations and was below detection limits at the 10-cm depth of the abyssal sediments of the Ierapetra Trench. Virus density in the sediment apparently reflected a gradient of particle fluxes and trophic conditions, displaying the highest values in the Sporades Basin. The low virus-to-bacterium ratios and their inverse relationship with station depth suggest that the role played by viruses in controlling deep-sea benthic bacterial assemblages and biogeochemical cycles is less relevant than in pelagic systems.